Proceedings of the Tenth ACM Symposium on Operating Systems Principles 1985
DOI: 10.1145/323647.323631
|View full text |Cite
|
Sign up to set email alerts
|

A trace-driven analysis of the UNIX 4.2 BSD file system

Abstract: We analyzed the UNIX 4.2 BSD file system by recording user-level activity in trace files and writing programs to analyze the traces. The tracer did not record individual read and write operations, yet still provided tight bounds on what information was accessed and when. The trace analysis shows that the average file system bandwidth needed per user is low (a few hundred bytes per second). Most of the files accessed are open only a short time and are accessed sequentially. Most new information is deleted or ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(79 citation statements)
references
References 10 publications
6
72
0
1
Order By: Relevance
“…Table 2 summarizes some studies founded on the understanding realistic system behavior. They fall into the categories of network systems [29,34,36,16,24,8], storage systems [35,16,32,13,19,10], and large scale data centers running computation paradigms including MapReduce [8,39,33,10,30,11]. Network and storage subsystems are key components for MapReduce.…”
Section: Prior Workmentioning
confidence: 99%
“…Table 2 summarizes some studies founded on the understanding realistic system behavior. They fall into the categories of network systems [29,34,36,16,24,8], storage systems [35,16,32,13,19,10], and large scale data centers running computation paradigms including MapReduce [8,39,33,10,30,11]. Network and storage subsystems are key components for MapReduce.…”
Section: Prior Workmentioning
confidence: 99%
“…In our research w e d o n o t i n vestigate read/write le access patterns, because most les are opened for either reading or writing, with few les updated 5,12]. We expect this to be especially true for the large les used in scienti c applications.…”
Section: Workload Modelmentioning
confidence: 99%
“…These applications typically push the leading edge of computing technology, such a s m ultiprocessors, placing tremendous demands on both CPU and I/O systems. Most le caching studies have examined generalpurpose workloads (e.g., 16]), where les are much smaller 12,5 ]. The parallel environment a n d w orkload raise a number of questions: Are caches useful for parallel scienti c applications using parallel le systems?…”
Section: Introductionmentioning
confidence: 99%
“…Measurements have shown that write sharing (i.e. two or more users writing the same file) happens only infrequently [125]. Thus, occasional conflicts may be tolerable if the availability of the data can be improved by relaxing the consistency model.…”
Section: Foundations and Related Workmentioning
confidence: 99%